2016
DOI: 10.1016/j.yebeh.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

NRSF and BDNF polymorphisms as biomarkers of cognitive dysfunction in adults with newly diagnosed epilepsy

Abstract: Cognitive dysfunction is a common comorbidity in people with epilepsy, but its causes remain unclear. It may be related to the etiology of the disorder, the consequences of seizures, or the effects of antiepileptic drug treatment. Genetics may also play a contributory role. We investigated the influence of variants in the genes encoding neuron-restrictive silencer factor (NRSF) and brain-derived neurotrophic factor (BDNF), proteins previously associated with cognition and epilepsy, on cognitive function in peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 93 publications
1
21
0
1
Order By: Relevance
“…Another property of recently established cognitive dysfunctions of epileptic patients is due to the establishment of new alterations of hippocampal neurons governed by REST. The results confirmed a role of REST polymorphism in the modulation of cognitive functions [39].…”
Section: Epilepsysupporting
confidence: 76%
See 1 more Smart Citation
“…Another property of recently established cognitive dysfunctions of epileptic patients is due to the establishment of new alterations of hippocampal neurons governed by REST. The results confirmed a role of REST polymorphism in the modulation of cognitive functions [39].…”
Section: Epilepsysupporting
confidence: 76%
“…During the last few years, the therapeutic potential of REST has attracted attention concerning both specific conditions and their deacetylases (examples in [57,58]). Recent therapeutic attempts have been included in numerous studies reporting neurodegenerative diseases [31][32][33][34] and epilepsy [38,39]. These studies, however, concerned primarily pathology, not therapies of diseases.…”
Section: Therapymentioning
confidence: 99%
“…Cognitive performance was evaluated in newly diagnosed epilepsy patients (baseline) and again 12 months later. They found that genetic variants of NRSF and BDNF were associated with greater impairment in memory functions and in psychomotor speed either at epilepsy diagnosis and in the subsequent follow up (e.g., 12 months later) …”
Section: Genetic Biomarkers Of Comorbiditiesmentioning
confidence: 99%
“…58 Such polymorphism is associated with high messenger RNA (mRNA) levels of BIN1. 58 Warburton et al 59 enrolled a subgroup of subjects from the Standard and New Antiepileptic Drugs (SANAD) trial and they evaluated the presence of polymorphisms in the neuron-restrictive silencer factor (NRSF) and brain-derived neurotrophic factor (BDNF) genes and their association with cognitive functions. Cognitive performance was FDG-PET coregistration with MRI in a patient with ASD, intellectual disability, and epilepsy.…”
Section: Genetic Biomarkers Of Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation